Diagnosis of myelomeningocele by three-dimensional ultrasound - Quispe, José (2015)
We report a case of myelomeningocele in the lumbar region diagnosed in a prenatal checkup at 13 weeks of gestation. Three-dimensional ultrasound examinations in the second and third quarters showed hydrocephalus, lemon sign and banana sign and polyhydramnios. The birth was at 38 weeks gestation by elective Caesarean section. Within 48 hours of birth was the surgical correction of the defect, with a favorable outcome and be given high at 6 days of age in good condition. Our impression is that the three-dimensional ultrasound is a technique that allows a more accurate diagnosis in prenatal diagnosis.